An investigation of stigmatizing attitudes towards people living with HIV/AIDS by doctors and nurses in Vientiane, Lao PDR. Issue 1 (December 2017) - Vorasane, Savina; Jimba, Masamine; Kikuchi, Kimiyo; Yasuoka, Junko; Nanishi, Keiko; Durham, Jo; Sychareun, Vanphanom
Abstract Background Despite global efforts, HIV-related stigma continues to negatively impact the health and well-being of people living with HIV/AIDS. Even in healthcare settings, people with HIV/AIDS experience discrimination. Anecdotal evidence suggests that healthcare professionals in the Lao People's Democratic Republic, a lower-middle income country situated in Southeast Asia, stigmatize HIV/AID patients. The purpose of this study was to assess HIV stigmatizing attitudes within Laotian healthcare service providers and examine some of the factors associated with HIV/AIDS-related stigma among doctors and nurses. Methods A structured questionnaire, which included a HIV-related stigma scale consisting of 17 items, was self-completed by 558 healthcare workers from 12 of the 17 hospitals in Vientiane. Five hospitals were excluded because they had less than 10 staff and these staff were not always present. The questionnaire was pre-tested with 40 healthcare workers. Descriptive statistical analysis was performed and comparisons between groups undertaken using chi-square test andt -test. Bivariate and multiple linear regression analyses were carried out to examine the associations between stigmatizing attitudes and independent variables. Results Out of the 558 participating healthcare workers, 277 (49.7%) were doctors and 281 (50.3%) were nurses. Nearly 50% of doctors and nurses included in the study had high levels of stigmatizing attitudes towards people living with HIV/AIDS. Across the different health professionals included in this study, lower levels of HIV/AIDS knowledge were associated with higher levels of stigmatizing attitudes towards people living with HIV/AIDS. Stigmatizing attitudes, including discrimination at work, fear of AIDS, and prejudice, were lower in healthcare workers with more experience in treating HIV/AIDS patients. Conclusions This study is the first to report on HIV/AIDS-related stigmatization among healthcare workers in Lao PDR. Stigmatizing attitudes contribute to missed opportunities for prevention, education and treatment, undermining efforts to manage and prevent HIV. Reversing stigmatizing attitudes and practices requires interventions that address affective, cognitive and behavioral aspects of stigma. Alongside this, health professionals need to be enabled to enact universal precautions and prevent occupational transmission of HIV.